PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DEWAN KOMISARIS, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP PENGUNGKAPAN INFORMASI PERTANGGUNGJAWABAN - Yulinia Erwanti; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
The practice of disclosure of social responsibility information plays an important role for the company because the company lives in a community environment and its potential activities have social and environmental impacts. The purpose of this study is to provide an overview of the practice of disclosure of social responsibility information conducted by manufacturing companies in Indonesia and to find out whether factors within the firm influence disclosure of information Corporate social responsibility of manufacturing.The population in this study is a manufacturing company listing on the Indonesia Stock Exchange (BEI) in 2013-2015. The manufacturing sector was chosen because this sector has the largest number of listings firms compared to other business sectors. In addition, this sector is a sector that has the widest range of stakeholders covering investors, creditors, governments, and the social environment so as to need to disclose social information. The total sample in this study amounted to 36 companies, with two years of observation period. The total observations made in this study were 44. This study used multiple regression analysis method to test the hypothesis.The results of this study indicate that the variable size of the company significantly influence CSRD on Manufacturing companies listed on the Indonesia Stock Exchange in 2013-2015. Profitability variables have no significant effect to CSRD on Manufacturing companies listed on Indonesia Stock Exchange in 2013-2015. The size of the board of commissioners (DKOM) has a positive and significant effect on CSRD on Manufacturing listed on the Indonesia Stock Exchange in 2013-2015. Audit committee size variables (UKAD) have no significant effect to CSRD on companies in Indonesia Stock Exchange. Audit quality variables (KUAD) have a negative effect on CSRD on Manufacturing companies listed in Indonesia Stock Exchange in 2013-2015.